Target plasma factor levels for personalized treatment in haemophilia: a Delphi consensus statement. Issue 3 (26th March 2017) - Iorio, A.; Iserman, E.; Blanchette, V.; Dolan, G.; Escuriola Ettingshausen, C.; Hermans, C.; Negrier, C.; Oldenburg, J.; Reininger, A.; Rodriguez‐Merchan, C.; Spannagl, M.; Valentino, L. A.; et al.
Abstract : Background: Prophylactic replacement with factor concentrate is the optimal treatment for persons with severe haemophilia to avoid or minimize bleeding. This ultimately prevents or reduces joint disease and improves life expectancy and quality of life towards values matching those in the normal population. However, uncertainty still exists around the optimal regimens to be prescribed for prophylaxis. An increasing number of treating physicians and patients are showing interest in patient‐tailored approaches to prophylaxis, which aim to harmonize the prophylaxis regimen with the patients' bleeding phenotype, levels of physical activity and a variety of other variables. Methods: A modified Delphi technique was adopted to generate consensus. The expert panel met in person to set the objectives, be trained on the Delphi technique and agree on the desired level of consensus. Three iterations were used to identify the targets, the scenarios and their combinations. Results: Twenty‐eight scenarios and eight target levels were identified and used to issue recommendations. The panel reached the desired level of consensus on positive or negative recommendations. Areas where consensus was not reached were identified and proposed as areas for future research. Prospective assessment of the validity of most of the proposed targets is recommended. Conclusions: We have generated, by expert consensus, target plasma levels of factor concentrate to be used to tailor treatment for persons with haemophilia.